Comparison of biomechanical parameters determining rowing performance in fixed and moving rowing ergometers - Kollias, I.; Chomatas, D.; Panoutsakopoulos, V. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Introduction Rowing ergometers are commonly used as a training modality aiming for a successful on-water rowing perfomance. Although benefits of using a moving rowing machine are documented [1, 2], static ergometers are still widely used. The purpose of the present study was to investigate the differences in selected dynamical and kinematical parameters determing rowing performance in an instrumented steady and moving rowing ergometer. Methods 10 national level male rowers (21.1±2.3yrs; 1.82±0.09m; 78.2±11.5kg) performed sessions of 12 full stroke cycles at maximum stroke rate on a CARE ROWPERFECT rowing ergometer. The testing proceedure was conducted under two ergometer conditions: a) with static resistance (SR; foot-stretchers were fixed on the rowing machine`s slide), and b) with moving resistance (MR; free foot-stretchers movement). The following instruments were attached on the rowing ergometer: a) a 2D strain-gaged dynamometers at the foot-stretchers, b) a Kistler 932-1B force-transducer (Kistler Instrumente AG Winterthur, Switzerland) attached between the ergometer chain and handle, c) two monoaxial strain-gaged dynamometers under the ergometer`s front and back base. The signals of the dynamometers were amplified and stored through A/D converter in a Pentium II PC (sampling frequency: 150Hz). An electronic encoder, part of a Microsoft mouse, was fixed in the axis of the chain`s gear to measure the relative position of the ergometer`s head and the handle. Subjects were filmed using a JVC GR-DLV 9600 EG (Victor Company, Japan) operating at a sampling frequency of 50Hz. Synchronization of kinematic and dynamic data was accomplished with Lagrangian interpolation, using the initial and final position of the push up phase, as defined by the encoder. A paired samples T-test (p<.05) was used to compare dynamic and kinematic parameters between SR and MR conditions. Results Comparison of SR and MR parameters is presented in Table 1; measured forces are expressed as % of body mass (BM) and joint angles represent the maximum value during the whole stroke cycle. MR stroke duration and recovery phase were significantly shorter (1.420.14sec vs 1.670.13sec, p<.001 and 0.740.12sec vs 0.930.12sec, p<.001, respectively) than SR. Stroke rate was larger in MR (42.84.7 vs 36.12.8, p<.001).